Antiasthmatic Effects of Hesperidin, a Potential Th2 Cytokine Antagonist, in a Mouse Model of Allergic Asthma - Seung-Hyung Kim; Bok-Kyu Kim; Young-Cheol Lee (Mediators of Inflammation)
Background and Objective. The features of asthma are airway inflammation, reversible airflow obstruction, and an increased sensitivity to bronchoconstricting agents, termed airway hyperresponsiveness (AHR), excess production of Th2 cytokines, and eosinophil accumulation in the lungs. To investigate the antiasthmatic potential of hesperidin as well as the underlying mechanism involved, we studied the inhibitory effect and anti-inflammatory effect of hesperidin (HPN) on the production of Th2 cytokines, eotaxin, IL-17, -OVA-specific IgE in vivo asthma model mice. Methods. In this paper, BALB/c mice were systemically sensitized to ovalbumin (OVA) followed intratracheally, intraperitoneally, and by aerosol allergen challenges. We investigated the effect of HPN on airway hyperresponsiveness, pulmonary eosinophilic infiltration, various immune cell phenotypes, Th2 cytokine production and OVA-specific IgE production in a mouse model of asthma. Results. In BALB/c mice, we found that HPN-treated groups had suppressed eosinophil infiltration, allergic airway inflammation, and AHR, and these occurred by suppressing the production of IL-5, IL-17, and OVA-specific IgE. Conclusions. Our data suggest that the therapeutic mechanism by which HPN effectively treats asthma is based on reductions of Th2 cytokines (IL-5), eotaxin, OVA-specific IgE production, and eosinophil infiltration via inhibition of GATA-3 transcription factor.